2022
DOI: 10.7324/jabb.2023.110209
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response in COVID-19 patients and novel design of lateral flow assay strip for simultaneous rapid detection of IgA/IgM/ IgG antibodies against the SARS-CoV-2 virus

Abstract: At the end of 2019, a novel coronavirus (CoV) appeared in Wuhan, China and has since spread to several countries and regions throughout the world. The disease caused by the novel CoV has been officially named CoV disease 2019 . This study provides additional data for the presence of anti-SARS-CoV-2 IgM and IgG antibodies in COVID-19 patients in Vietnam. The study also presents the development of a lateral flow immunoassay (LFA) strip for rapid simultaneous detection of the IgA/IgM/IgG antibodies against the SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The activity of purified IgG antibodies was determined by the ELISA method [13]. Briefly, 1 µg protein of rubella virus in 50 mM carbonate buffer pH 9.6 was coated on each well of the microtiter plate at 4°C overnight.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…The activity of purified IgG antibodies was determined by the ELISA method [13]. Briefly, 1 µg protein of rubella virus in 50 mM carbonate buffer pH 9.6 was coated on each well of the microtiter plate at 4°C overnight.…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Interestingly, the authors found that the visibility of the T-and C-lines were not affected by the presence of anticoagulants such as TSC, Heparin, and EDTA in the spiked negative, weak positive, and strong positive samples. LFA was also assessed for cross-reactivity with other virus types where the T-line did not show any visible response [118].…”
Section: Detection Of Iga Igg and Igm Antibodies In Serum And Nasal S...mentioning
confidence: 99%